ANTI-ALOPECIA ACTIVITY OF MORINGA (MORINGA OLEIFERA LAMK.) SEED OIL AGAINST DIHYDROTESTOSTERONE-INDUCED RABBITS - KORASSA, YULIUS BAKI; SAPTARINI, NYI MEKAR; MUSTARICHIE, RESMI; HENDRIANI, RINI; OLA, ANTONIUS R. B.; NOVICADLITHA, YOAN; KAPITAN, LELY A V (International Journal of Applied Pharmaceutics, 2023)
Objective: Alopecia is a condition where there is hair loss or no growth of hair, which can occur as a result of stress, heredity, hormonal factors or due to certain diseases such as diabetes mellitus. This study aimed to determine the anti-alopecia activity of moringa seed oil against rabbits induced by dihydrotestosterone (DHT). Methods: The methods used was the alopecia rabbit model according to Matias with moringa seed oil concentrations of 7.5, 10 and 12.5%, positive control (0.1% finasteride) and negative control (1% tween 80) with parameters hair length and hair weight test. Results: Results showed that moringa seed oil concentrations of 7.5, 10 and 12.5% had anti-alopecia activity with average hair length of 3.4±0.17, 3.9±0.20 and 4.5±0.28 cm, respectively and average hair weight of 118±23.148±30.9 and 175±47.2 mg respectively. Conclusion: Moringa seed oil concentration of 12.5% had optimal activity for developing as anti-alopecia based on the statistical analysis value of hair length (125x10-3>0.05) was not significantly different while hair weight (3x10-3<0.05) was significantly different from the positive control of 0.1% finasteride.